Potential Analysis and Development Strategies Based on Zoning For Beef Cattle Farming in Kepulauan Bangka-Belitung Province - Muhammad Taufiq Alamsyah; Siti Andarwati; Tri Anggraeni Kusumastuti; Panjono Panjono (Buletin Peternakan, 2022)
This research was aimed in detemining the potency mapping and development strategies based on zoning for beef cattle farming in Kepulauan Bangka Belitung Province. This research was implemented by using two-stages survey method. The first stage was analyzing and making regional potency mapping from secondary data with potential index analyses. The second stage was observing the results of the observation, an in-depth interview, and focus group discussion towards 42 respondents consisted of 14 cattle farmers, 5 cattle sellers, 5 agriculture agency officers, and 18 officials who were in charge of the cattle function in regency/city. Purposive sampling was used to choose respondents. Meanwhile, the data analysis used SWOT analysis. The results of potency mapping showed that Bangka had the highest index (the most potential). Pangkalpinang had the lowest index (potential). The qualitative SWOT analysis resulted in the strategy of SO (Strength-Opportunity), WO (Weakness-Opportunity), ST (Strength-Treat), and WT (Weakness-Threats). Qualitative analysis of SWOT showed the internal factor -0,153 (x) and external factor 0,34 (y). The strategies were in quadrant III; changing the policies by minimizing the weakness to take advantage of opportunities. The analysis for RTRW documents and the result of SWOT analysis generated 6 (six) zones and development priorities. Thus, the development plan of beef cattle consisted of priority zones: 1). I: production center and product processing in Bangka Tengah; 2) II: Cattle farmer integration in Bangka, Bangka Barat, and Belitung Timur; 3) III: Cattle farming in a previously ex-mining land in Bangka, Bangka Barat, and Belitung Timur; 4) IV: production center with local based feed production in Bangka Selatan; 5) V: Modern cattle farm with technology-based in Pangkalpinang; 6) VI: Animal farm with agrotourism based in Pangkalpinang and Belitung.